Restraint Management in Psychiatric Patients at RSKD Dadi South Sulawesi Province - A Nur Anna AS; St. Suarniati St. Suarniati; Abdul Halim (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Mental health is also defined as well-being when a person can realize his potential. This mechanism is suitable against stressors, productive, and capable of contributing to society. The prevalence of psychotropy in Indonesia is around 7 per mile. Schizophrenia can cause the patient to behave aggressively, which can cause injury to himself or others, including the nurse. The study aimed to determine the effectiveness of restraint management training for psychiatric patients at Dadi Special Regional Hospital (RSKD) in South Sulawesi Province. This study was a quasi-experiment on samples of intervention groups to see differences in rates between two groups before and after training and correlation. The result showed that attitudes before and after training with a significance value of 0,000 (p-value<0,005), and a 95% IK value had a significant ratio difference of 2,25–5,98, the result of knowledge and skills using wilcoxon test before and after training showed statistically meaningful result with a value of p=0,000, while the result of relationship between knowledge and a skill of 0,334 using the correlation test indicated a weak interpretation of correlation, and the p-value of 0,150 (p-value>0,05) showed no significance. This study concluded that there was a meaningful value in knowledge, skills, and attitudes before and after training, and significant mean differences did exist.